2000
DOI: 10.22358/jafs/68062/2000
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rolled rape seeds on milk composition and lactational responses

Abstract: Forty-five multiparous cows (74-146 d after calving) were blocked into 3 groups of 15 animals on the basis of calving date and milk yield. Within each group the cows were allotted at random to treatment sequences in a 3x3 Latin square design. Cows were fed a ration composed of pasture, maize silage and meadow hay. Treatments were: control (CK), 6 kg concentrate without rolled rape seeds (WRS), MR-5 kg concentrate and 0.7 kg WRS and HR-4 kg concentrate and 1.4 kg WRS. The administration of 1.4 kg (HR) rolled ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…Garnsworthy (1997) concluded that increasing the intake of fat may increase the proportion of unsaturated fatty acids in milk fat, since the de novo synthesis of short-chain fatty acids is reduced and these are all saturated. Similar results, using other types of vegetable fat, were obtained by Shingoethe et al (1996) and Nowak and Potkanski (2000). Banks (1987) pointed out that higher levels of oleic acid in milk fat are due either to increased dietary C 181 as a result of partial hydrogenation in the rumen, or increased desaturation of C lg0 in the gut wall and mammary glands.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Garnsworthy (1997) concluded that increasing the intake of fat may increase the proportion of unsaturated fatty acids in milk fat, since the de novo synthesis of short-chain fatty acids is reduced and these are all saturated. Similar results, using other types of vegetable fat, were obtained by Shingoethe et al (1996) and Nowak and Potkanski (2000). Banks (1987) pointed out that higher levels of oleic acid in milk fat are due either to increased dietary C 181 as a result of partial hydrogenation in the rumen, or increased desaturation of C lg0 in the gut wall and mammary glands.…”
Section: Discussionsupporting
confidence: 81%
“…Strzetelski et al (1999) reported a tendency to supplement cows' diets with evening primrose seeds (Oenothera paradoxa) to increase milk production and fat content. Also Nowak and Potkanski (2000) recorded a non-significant increase in the yield of milk after the addition of 1.4 rolled rape seed. In the present study on dairy cows receiving supplemental fat from EMT, a significant increase in milk fat content and daily milk fat production was found, suggesting that calcium and sodium bicarbonate reduced the negative effects of unsaturated and unprotected fatty acids on fibre digestion in the rumen and rumen fermentation.…”
Section: Discussionmentioning
confidence: 94%
“…Strzetelski et al (1998), McNamee et al (2002 and Givens et al (2003) reported that feeding cows with rapeseed significantly enhanced the oleic and stearic acid contents in milk fat at the expense of C8 to C16 saturated FA. Similarly, Nowak and Potkański (2000) reported that feeding rolled rapeseed increased the concentration of oleic acid in milk fat at the expense of short-and medium-chain FA, i.e. FA predominantly synthesized in the mammary gland.…”
Section: Discussionmentioning
confidence: 87%
“…Energy insufficiency, often occurring in the first months of lactation, is supplemented with the addition of tallow [15] , vegetable oil of oil plant seeds and waste fats [17,25] . There are also applied protected fats -neutral to the rumen environment -lime soaps of fatty acids [7,25,26] , seeds of oil plants subjected to a heating or extrusion process [12 ,26] and prilled fats [16] .…”
Section: Introductionmentioning
confidence: 99%
“…There are also applied protected fats -neutral to the rumen environment -lime soaps of fatty acids [7,25,26] , seeds of oil plants subjected to a heating or extrusion process [12 ,26] and prilled fats [16] . The fats of plant origin do significantly differ from the ones of animal origin in the kind of fatty acids they contain [2,6,16] .…”
Section: Introductionmentioning
confidence: 99%